Observation of the flexoelectricity of a SrTiO3 single crystal by x-ray absorption and emission spectroscopies. (24th November 2016) - Lu, C; Nakajima, N; Maruyama, H
Abstract: Flexoelectricity, defined as the spontaneous electric polarization in a dielectric material induced by a strain gradient, is investigated from the microscopic viewpoint by x-ray spectroscopy. A single crystal SrTiO3 sample was used as a test system in order to reveal the appearance of the electric dipole moment by simple bending of the crystal. The spectral change characteristic of ferroelectric transition in SrTiO3 was not observed in the Ti K-edge absorption spectra. Instead, the gradual decrease (increase) of the post-edge feature (pre-edge structure) by bending was qualitatively explained using theoretical calculations that assumed the presence of oxygen vacancies and a slight crystal distortion. This assumption is also supported by the broadening of a tiny charge-transfer peak in the Ti K β resonant emission spectra. Therefore, it was revealed that the flexoelectric effect in SrTiO3 is easily drowned out through local imperfection induced by crystal deformations and cracks.